CORRECTION OF IMMUNE SYSTEM CELLS BY THE HERBAL PREPARATION GULZOR BALM IN IRRADIATED ANIMALS WITH DIFFERENT ACETYLATION TYPES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Secondary immunodeficiency (SID) represents a dysfunction of the immune system that develops during the late postnatal period or in adulthood. It is characterized by impaired differentiation, proliferation, and adaptation of immune cells and is not associated with genetic defects. Irreversible SID may develop as a result of HIV infection, exposure to high doses of ionizing radiation, toxic effects on the hematopoietic system, lymphoproliferative and other malignant disorders, or severe bacterial, viral, and fungal infections such as tuberculosis and systemic mycoses.